2017
DOI: 10.3390/ijms18040332
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Curcumin and Lycopene or Bixin in Yoghurt on Inhibition of LDL Oxidation and Increases in HDL and Paraoxonase Levels in Streptozotocin-Diabetic Rats

Abstract: Combination therapy using natural antioxidants to manage diabetes mellitus and its complications is an emerging trend. The aim of this study was to investigate the changes promoted by treatment of streptozotocin (STZ)-diabetic rats with yoghurt enriched with the bioactives curcumin, lycopene, or bixin (the latter two being carotenoids). Antioxidants were administered individually, or as mixtures, and biomarkers of metabolic and oxidative disturbances, particularly those associated with cardiovascular risk, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 68 publications
7
52
1
1
Order By: Relevance
“…The overproduction of ROS and the decreased levels of antioxidant defenses contribute to the establishment of oxidative stress in DM (Maritim, Sanders, & Watkins, ). In agreement with this, DYOG rats had high levels of oxidative damage biomarkers, including plasma TBARS (Figure a) and hepatic PCO (Figure b) and low activity of antioxidant enzymes (Figure ), corroborating the results from previous studies (Arcaro et al, ; Assis et al, ). Structural modifications due to oxidative or glycative stress may explain the low activity of antioxidant enzymes in diabetes (Pigeolet et al, ; Yan & Harding, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The overproduction of ROS and the decreased levels of antioxidant defenses contribute to the establishment of oxidative stress in DM (Maritim, Sanders, & Watkins, ). In agreement with this, DYOG rats had high levels of oxidative damage biomarkers, including plasma TBARS (Figure a) and hepatic PCO (Figure b) and low activity of antioxidant enzymes (Figure ), corroborating the results from previous studies (Arcaro et al, ; Assis et al, ). Structural modifications due to oxidative or glycative stress may explain the low activity of antioxidant enzymes in diabetes (Pigeolet et al, ; Yan & Harding, ).…”
Section: Discussionsupporting
confidence: 91%
“…The antidiabetic activity of curcumin has been well documented in both type 1 (Gutierres et al, ) and type 2 (Shao et al, ) DM models, improving not only the levels of glycemia but also those of dyslipidemia and tissue damage markers. Previous studies carried out by groups from our laboratory (Arcaro et al, ; Assis et al, ) and by others (Ghosh, Bhattacharyya, Rashid, & Sil, ) have found that the treatment of diabetic rats with curcumin is able to reduce in vivo oxidative stress. These findings identify curcumin as a promising adjunct to insulin therapy for diabetes.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The hypothesis is that lycopene could protect the biomolecules, such as lipids, proteins, and DNA, against being oxidized via blocking the damage from ROS (Rao, Ray, & Rao, ). In different disease models, lycopene has been reported possessing capacities in ameliorating oxidative stress by reducing malondialdehyde (MDA), TNF‐α, and oxidized low‐density lipoprotein (ox‐LDL) (Assis et al., ; Murillo, DiMarco, & Fernandez, ; Pierine et al., ; Yin et al., ). Besides its antioxidant properties, lycopene was also reported to possess biological activities, such as facilitating gap junction communication, stimulating the immune system, modulating endocrine‐mediated pathways, and regulating cell cycle (Rao et al., ).…”
Section: Introductionmentioning
confidence: 99%